Efektivitas Penggunaan Perangkat Lunak E-Surveillance dalam Meningkatkan Kepatuhan dan Akurasi Pengisian Data Pasien di Ruang ICU di x Rumah Sakit Yogyakarta - Bangun Kurniady (Jurnal Admmirasi, 2020)
This study aims to determine the effectiveness of the use of e-surveillance applications in improving the collection and accuracy of filling Patient Infection data. The sample used was medical nurses on duty in the ICU room of PKU Muhammadiyah Gamping Hospital in Yogyakarta. The technique used is linear regression on the pretest and posttest data with the help of the IBM SPSS 25 application program. The results of the study: 1. Gives a significant score on the pretest and posttest. 2. Gives a significant difference in score on the pretest and posttest accuracy of medical personnel in performing the task of recording patient data using e-surveillance application software. 3. It turned out that the socialization of applying e-surveillance software to nurse medical staff in the ICU room proved to be effective in increasing the success and accuracy of nurses medical officers